In vitro targeted imaging and delivery of camptothecin using cetuximab-conjugated multifunctional PLGA-ZnS nanoparticles. (April 2012) - Deepagan, Veerasikku Gopal; Sarmento, Bruno; Menon, Deepthy; Nascimento, Ana; Jayasree, Aswathy; Sreeranganathan, Maya; Koyakutty, Manzoor; Nair, Shantikumar V; Rangasamy, Jayakumar
Background: Targeted cancer therapy has been extensively developed to improve the quality of treatment by reducing the systemic exposure of cytotoxic drug. Polymeric nanoparticles with conjugated targeting agents are widely investigated because they offer tunability in particle size, drug release profile and biocompatibility.Materials & methods: Here, we have prepared targeted multifunctional nanoparticles composed of a poly(lactic- co -glycolic acid) matrix, ZnS:Mn 2+ quantum dots and camptothecin, and targeted them to EGF receptor overexpressing cells with a cetuximab antibody.Results: Physicochemical characterization of multifunctional nanoparticles showed stable particles with sizes of <200 nm. In vitro drug release and blood contact studies showed a sustained release profile, with limited hemolysis. In vitro cytotoxicity and cell uptake studies were carried out in A549, KB and MFC-7 cell lines using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, FACS, fluorescent microscopic images and spectroflourimetry.Conclusion: Our studies revealed higher camptothecin activity and uptake in cell lines that overexpress the EGF receptor. All these results suggest that anti-EGF receptor cetuximab-conjugated poly(lactic- co -glycolic acid) multifunctional nanoparticles can be used as a potential nanomedicine against cancer.